Contribution of Triple-Phase Boundary Reaction in Cathodic Reaction of Solid Oxide Fuel Cell. (30th May 2017) - Fujimaki, Yoshinobu; Mizuno, Keita; Kimura, Yuta; Nakamura, Takashi; Bagarinao, Katherine Develos-; Yamaji, Katsuhiko; Yashiro, Keiji; Kawada, Tatsuya; Iguchi, Fumitada; Yugami, Hiroo; Amezawa, Koji
Abstract : The cathodic reaction of a solid oxide fuel cell (SOFC) was investigated by 18 O/ 16 O isotope exchange with/without polarization and isotopic distribution analysis by second ion mass spectroscopy. In order to elucidate the contribution of triple phase boundary (TPB) reaction while eliminating the influence of the electrode microstructure, a patterned thin film electrode was used as a model cathode. La0.6 Sr0.4 CoO3- δ was chosen as a model material exhibiting mixed ionic and electronic conduction. A slight increase in the 18 O ratio was observed within 20 µm from the electrode/electrolyte interface under a constant cathodic polarization of 220 mV at 973 K in 1 bar of P (O2 ). Such an increase in the 18 O ratio was considered to be caused by the electrochemical oxygen incorporation. The contribution of the TPB reaction to the total cathode reaction was not clearly observed at least in applied experimental conditions.